2021
DOI: 10.1002/adem.202001416
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Electrorheological Properties of Peanut‐Like Hollow Core–Shell Structure TiO2@SiO2 Nanoparticles

Abstract: Although titanium oxide has a high dielectric constant, ordinary titanium oxides are not a good electrorheological (ER) fluid material. Herein, hollow peanut-like titanium oxide spheres are synthesized by hydrothermal method, and then coated with silicon oxide to form core-shell hollow TiO 2 @SiO 2 spheres. The structure is characterized by different methods, and the TiO 2 @SiO 2 composite particles are dispersed in silicone oil to prepare an ER suspension. The ER effect of 10% TiO 2 @SiO 2 -based ER fluid und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Properties of both the dispersed phase and the continuous liquid materials are key factors affecting their properties in the research into ER components. Researchers have paid more attention to developing dispersed phase materials with high ER properties because of the greater diversity and designability of the dispersed phase materials. The types of the dispersed phase materials are generally divided into inorganic materials, organic materials, , and composite materials. , Among a variety of inorganic materials, titanium dioxide (TiO 2 ), as a kind of transition-state oxide with relatively high dielectric properties and polarizability, is a promising high-performance ER material. However, the paucity of active groups on the surface of pure TiO 2 nanoparticles and their low conductivity limit the polarizability of the particles, which causes pure TiO 2 to have poor ER properties. , When the ER fluids are composed of TiO 2 and a small amount of water, the system will exert a better ER effect. This is because water acts as a polar molecule to provide permanent dipoles from forming on the surface of the particles.…”
Section: Introductionmentioning
confidence: 99%
“…Properties of both the dispersed phase and the continuous liquid materials are key factors affecting their properties in the research into ER components. Researchers have paid more attention to developing dispersed phase materials with high ER properties because of the greater diversity and designability of the dispersed phase materials. The types of the dispersed phase materials are generally divided into inorganic materials, organic materials, , and composite materials. , Among a variety of inorganic materials, titanium dioxide (TiO 2 ), as a kind of transition-state oxide with relatively high dielectric properties and polarizability, is a promising high-performance ER material. However, the paucity of active groups on the surface of pure TiO 2 nanoparticles and their low conductivity limit the polarizability of the particles, which causes pure TiO 2 to have poor ER properties. , When the ER fluids are composed of TiO 2 and a small amount of water, the system will exert a better ER effect. This is because water acts as a polar molecule to provide permanent dipoles from forming on the surface of the particles.…”
Section: Introductionmentioning
confidence: 99%
“…46 The absorption peaks at 1023 and 900 cm ), which suggests that the calcined sample is composed of a TiO 2 −SiO 2 molecular hybrid framework. 47 In addition, XPS analysis (Figure 5) was involved to evaluate the compositions of TS-HSs before and after calcination. Before calcination, the binding energies are located at 101.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that the TESPT organosilica source and the TDAA titanium source are co-condensed, forming a hybrid TiO 2 –SiO 2 framework. After annealing, the characteristic peaks at 2922, 2853, and 1245 cm –1 disappear, leaving only the peaks with Si–O–Si (1090 cm –1 ), Ti–O–Si (936 cm –1 ), and Ti–O–Ti (640 cm –1 ), which suggests that the calcined sample is composed of a TiO 2 –SiO 2 molecular hybrid framework …”
Section: Resultsmentioning
confidence: 99%
“…It is observed that no sedimentation after ageing for 240 h, while pure PIL microbead suspension shows 60% sedimentation. This enhanced suspension stability can be attributed to the hollow structure of SiO x -PIL microcapsules, which not only decreases the apparent density, [36][37][38][39] but also provides better affinity towards the silicone oil by SiO x . Figure 3b presents the electric field-induced shear stress (Δ𝜏) of ER suspensions of SiO x -PIL microcapsules under electric fields.…”
Section: Resultsmentioning
confidence: 99%